A case report of ‘Two-Hit’ digenic mutations in PAH: role of PADN in management - Zai-qiang Zhang; Zai-qiang Zhang; Zhou-qiang Qin; Zhou-qiang Qin; Sheng-kui Zhu; Sheng-kui Zhu; Yu-hong Zuo; Yu-hong Zuo; Jia-wang Ding; Jia-wang Ding (Frontiers in Pharmacology, 2025)
BackgroundPulmonary arterial hypertension (PAH) is a severe cardiopulmonary disorder characterized by progressive elevation of pulmonary vascular resistance, resulting to right ventricular dysfunction and premature mortality. Although genetic mutations are increasingly recognized in PAH pathogenesis, cases involving digenic mutations remain exceptionally rare.Case presentationWe report the case of a 47-year-old female presenting with a 5-year history of exertional dyspnea, which progressively worsened over the preceding 2 months. Diagnostic imaging revealed pulmonary artery dilatation and right heart enlargement, and right heart catheterization confirmed PAH with a mean pulmonary arterial pressure of 43 mmHg. Whole exome sequencing identified a novel heterozygous mutation in FLNA (c.4754C>T, p.Thr1585Met) and a known heterozygous mutation in MMACHC (c.609G>A, p.Trp203Ter). The patient was initiated on PAH-specific therapy and pulmonary artery denervation (PADN) treatment. Over a 2-year follow-up period, her symptoms significantly improved, with no evidence of heart failure progression.ConclusionThis case highlights a rare instance of PAH associated with digenic mutations in FLNA and MMACHC. The patient demonstrated a favorable response to targeted PAH therapy and PADN treatment, highlighting the importance of genetic screening and personalized treatment strategies in PAH management.